SISTEM INFORMASI RESERVATION KAMAR HOTEL BERBASIS WEB - Ahmad Nuzuli Rahman (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The purpose of the research was to develop a reservation system and upload all facility, agenda, and promotion-related information to the internet. If the research was successful, it could later assist in promoting services to the general public and make it simpler for the general public to obtain information by visiting the website. A web-based reservation information system was developed as part of this study. Where in system development, tools like flowcharts and entity relational diagrams (ERDs), as well as the programming languages PHP, JQuery, and java script with a MySQL database, are utilized. Regarding the methods for gathering data through field studies, which include interviews, direct observation (observation), and literature review, This study produces information in the form of dynamic web-based facilities, agendas, and promotions in addition to an online registration system.